Design, Synthesis, and Herbicidal Activity Evaluation of Novel Aryl-Naphthyl Methanone Derivatives - Fu, Ying; Wang, Kui; Wang, Peng; Kang, Jing-Xin; Gao, Shuang; Zhao, Li-Xia; Ye, Fei (Frontiers in Chemistry, 2019)
4-Hydroxyphenylpyruvate dioxygenase (HPPD) is one of the most vital targets for herbicides discovery. In search for HPPD inhibitors with novel scaffolds, a series of aryl-naphthyl methanone derivatives have been designed and synthesized through alkylation and Friedel-Crafts acylation reactions. The bioassay indicated some of these compounds displayed preferable herbicidal activity at the rate of 0.75 mmol/m2 by post-emergence application, in which compound 3h displayed the best herbicidal activity. The molecular docking showed that compound 3h could bind well to the active site of the AtHPPD. This study shows that aryl-naphthyl methanone derivatives could be a potential lead structure for further development of novel herbicides.